Periodontal treatment needs among dental and non dental Iraqi students (A comparative study) (Mustansiria Dental Journal, 2018)
The direct relation between periodontal disease and the oral hygiene level on one hand and the level of education on the other hand were repeatedly proved throughout a large number of epidemiologic periodontal studies. Based on this fact, one can conclude that the periodontal treatment need among highly educated individuals (as university students) seems to be less than that of individuals with low educational level, but a question that may arise in this area is: Does the treatment need among dental students differ from that of their colleagues in other studies or not? The present research aimed at providing an answer for this question. Three hundreds university students (150 dental &150 non dental) were examined by using CPITN and the data were analyzed statistically. Results indicated that in general the periodontal treatment need was comparable between dental and non dental students in this social class. Results also indicated that programs aimed at improvement of oral hygiene of this social class may be applicable in our community, the matter that calls for full cooperation from the health authorities to carry out a national campaign directed toward this social class.